A new species of Limnephilus (Trichoptera: Limnephilidae) from the Mongolian Altai Mountains - Chuluunbat, Suvdtsetseg; Rhee, Jae-Sung; Morse, John C.; Tsagaan, Khongorzul; Erdene-Ochir, Chantsalmaa (Zootaxa, 2026)
Twenty-five species of the genus Limnephilus are known from Mongolia, with one species endemic to the country, Lake Hovsgol. Here, a new species, Limnephilus altaicus is described from both sexes, originating from the western part of the Mongolian Altai Mountains. The male genitalia of L. altaicus sp. nov. are characterized by superior appendages that are narrow basally and acute apically in dorsal view with long setae subapicodorsally and by the phallus and parameres that are short, thick, and upturned, each paramere with spines apically. The female genitalia of L. altaicus sp. nov. are distinguished by a concolorous segment X and tergum X being approximately as long as appendages of segment X. The distinctiveness of this species is supported by phylogenetic evidence derived from both molecular and morphological analyses.